Cardiac geometry, function and mechanics in left ventricular non-compaction cardiomyopathy with preserved ejection fraction - Guigui, Sarah A.; Horvath, Sofia A.; Arenas, Ivan A.; Mihos, Christos G. (Journal of echocardiography, 2022)
Background Left ventricular non-compaction (LVNC) cardiomyopathy in adults has primarily been studied with a phenotypic expression of low ejection fraction (EF) and dilated cardiomyopathy; however, data on LVNC with preserved EF is scarce. The present study aimed to evaluate cardiac geometry and mechanics in LVNC patients with preserved EF. Methods A retrospective cohort study of patients diagnosed with LVNC and a preserved EF between 2008 and 2019 was performed. LVNC was defined according to the presence of established transthoracic 2D echocardiographic (TTE) criteria as follows: (1) prominent LV trabeculations with deep recesses; (2) bi-layered myocardial appearance; and, (3) systolic non-compacted:compacted ratio≥ 2. Subjects were matched 1:1 to controls without LVNC referred for routine TTE. Geometric, functional and mechanics parameters were analyzed in the two cohorts using 2D and speckle-tracking TTE. Results Seventeen patients with LVNC and preserved EF were identified. Compared with controls, patients with LVNC had similar LV systolic function and chamber dimensions, but a larger mass and relative wall thickness, and more abnormal LV geometry (76% vs. 18%, p = 0.002), LA remodeling, and pulmonary hypertension. Global longitudinal strain was significantly decreased (-15.4 ± 3.2 vs. -18.9 ± 2.8%, p =  < 0.01) and the prevalence of rigid body rotation was significantly increased (57% vs. 14%, p = 0.05) in the LVNC population. The peak twist values were comparable in both cohorts. Conclusions Impaired LV geometry and longitudinal mechanics, as well as increased myocardial stiffness as expressed by rigid body rotation, characterize LVNC with preserved EF when compared with controls.